Advanced AutoCAD training for vocational high school teachers and laboratory assistants - Abdullah, Syarif; Satria, Dhimas; Caturwati, Ni Ketut; Dwinanto, Dwinanto; Lusiani, Rina; Ula, Shofiatul; Yusuf, Yusvardi; Erwin, Erwin; Listijorini, Erny; Notonegoro, Hamdan Akbar; Susilo, Sidik; Haryadi, Haryadi (Journal of Community Service in Science and Engineering (JoCSE), 2023)
This community service program is carried out as drawing training using Advanced AutoCAD for teachers and laboratory assistants at a vocational high school in Serang Regency, namely SMK YP Fatahillah 1 Kramatwatu. This program is carried out to improve vocational students' ability and readiness in the world of work and industry. The training materials provided in this training are introductions, drawings, sketches, modifications, and 3D AutoCAD. This training activity is implemented using the method of presentation, tutorial, practice, discussion, question and answer, and exercises. The results of the training showed an increase in the ability of participants in the introduction of the AutoCAD application. The achievements of the activities in this training were realized by the results of the participants' work after the training. Program pengabdian kepada masyarakat ini dilakukan dalam bentuk pelatihan menggambar menggunakan Advanced AutoCAD pada guru dan laboran di salah satu sekolah menengah kejuruan di Kabupaten Serang, yaitu SMK YP Fatahillah 1 Kramatwatu. Program ini dilakukan untuk meningkatkan kemampuan dan kesiapan siswa SMK dalam menghadapi dunia kerja dan industri. Materi pelatihan yang diberikan pada pelatihan ini yaitu tentang introductions, drawing, sketch, modify dan 3D AutoCAD. Pelaksanaan kegiatan pelatihan ini dilakukan dengan metode presentasi, tutorial, praktik, diskusi, tanya jawab, dan latihan. Hasil pelatihan didapatkan peningkatan kemampuan peserta dalam pengenalan aplikasi AutoCAD. Capaian kegiatan pada pelatihan ini diwujudkan dengan hasil kerja para peserta setelah pelatihan.